Effects of graphic organizers on students’ reading engagement of Ethiopian grade five students - Mehari, Yewulsew Melak; Bewuket, Haile Kassahun; Akalu, Sualih Mussa (Ethiopian Journal of Language, Culture and Communication, 2026)
Reading engagement remains a major challenge among Grade Five EFL learners in Ethiopia, where limited exposure to English texts and teacher-centered instruction often reduce students’ motivation and active participation in reading. To address this gap, the present study examined the effect of graphic organizers on students’ behavioral, cognitive, and emotional engagement in reading. A quasi-experimental pre-test–post-test design was employed, involving 98 students sampled from a single school. The study was conducted over a seven-week intervention period. The experimental group (49 students) received reading instruction using instructional materials prepared by the researchers, which incorporated various graphic organizers, such as concept maps, Venn diagrams, Know–Want to Know–Learned charts, story maps, and cause-and-effect charts, applied to reading passages sourced directly from the Grade Five English textbook. In contrast, the comparison groups (49 students) were taught through teacher-centered methods using the textbook’s standard activities without any graphicorganizer. Quantitative data were collected through a reading engagement questionnaire, and qualitative insights were gathered via focus group discussions to complement and deepen the interpretation of results. The post-test findings revealed that the experimental group (M = 111.67) demonstrated significantly higher engagement than the comparison group (M = 85.57), with a mean difference of 26.10, t (96) = 12.47, p < .001, and a large effect size (Cohen’s d = 2.97, η² = 0.69). Qualitative findings supported these results, showing that students found reading more interesting, interactive, and meaningful when graphic organizers were used. Overall, the study concludes that integrating graphic organizers into EFL reading instruction enhances students’ behavioral, cognitive, and emotional engagement, suggesting their strong potential for promoting active, student-centered learning and improving reading comprehension in primary classrooms.